Renal and hepatic function in rats treated with cyclosporin A in combination with gentamicin or cephalosporin antibiotics. - Whiting, P. H. (1983)
Sprague-Dawley rats received cyclosporin A (25 mg/kg) together with either the aminoglycoside gentamicin (50 mg/kg) or one of 3 cephalosporin antibiotics (100 mg/kg) daily for 14 days. Only minor impairment of renal or hepatic function was observed when either cyclosporin A or gentamicin was given on its own and no abnormality was seen in response to cephalosporins. However, concomitant administration of cyclosporin A and gentamicin caused acute renal failure, accompanied by cyclosporin A-induced damage to the proximal straight tubule and gentamicin-induced proximal convoluted tubular cell necrosis. In contrast, the structural abnormalities present in the 3 groups given cephalosporins in addition to cyclosporin A were attributable only to the immune suppressant. Liver functional changes previously found only at higher doses of cyclosporin A were observed in the cyclosporin A/gentamicin group and there was some evidence of possible interactions between cyclosporin A and each cephalosporin affecting liver function. The results indicate that treatment of infection with cephalosporin antibiotics or a less nephrotoxic aminoglycoside is preferable to gentamicin in cyclosporin A-treated patients.